Recycling endeavours among the P.P.R residents in Kuala Lumpur : a qualitative approach / Mohd Rozaimy Ridzuan ... [et al.] - Mohd Rozaimy, Ridzuan; Noor Amira Syazwani Abd Rahman, Abd Rahman; Nur Syafiqah, Hussin; Naqiah, Awang (Universiti Teknologi MARA, Perak, 2017)
The involvement of householdsin the recycling activity in the last decade has been perceived as an effective way to reduce the amount of solid wastes in the landfill areas as well asto reuse the materials. The recycling practice among the public is very crucial in order to reduce the problem of overwhelming landfills and energy. The ever-increasing flow of household waste is an enormous environmental problem in many countries. By looking at the tremendous amount of solid wastes, Malaysia needs public participation in solid waste management by recycling the unused materials. Thus, the present study explores predictors that lead households to participate in recycling activities. A qualitative approach is employed in this study where key stakeholders were interviewed in orderto get their different perspectives with regard to recycling activities among households. This study is vital as it supplements the information to the existing body of knowledge on households’recycling activity in Malaysia.